2021
DOI: 10.1080/19490976.2021.1897211
|View full text |Cite
|
Sign up to set email alerts
|

Limosilactobacillus fermentum JL-3 isolated from “Jiangshui” ameliorates hyperuricemia by degrading uric acid

Abstract: Recent studies into the beneficial effects of fermented foods have shown that this class of foods are effective in managing hyperuricemia and gout. In this study, the uric acid (UA) degradation ability of Limosilactobacillus fermentum JL-3 strain, isolated from “Jiangshui” (a fermented Chinese food), was investigated. In vitro results showed that JL-3 strain exhibited high degradation capacity and selectivity toward UA. After oral administration to mice for 15 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
108
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 74 publications
6
108
0
Order By: Relevance
“…The activities of XOD were suppressed via a collaborative mechanism through some unknown specific effector substance secreted by Limosilactobacillus fermentum JL-3 in hyperuricemia mouse experiments. 25 A study of probiotics found that the excretion of uric acid in the urine increased by approximately 15% due to changes in xanthine and hypoxanthine levels after feeding Saccharomyces cerevisiae to lambs. 51 Lactobacillus brevis DM9218 was isolated from traditional fermented Chinese food and decreased serum uric acid levels and hepatic XOD activity in fructose-mediated hyperuricemia mice.…”
Section: The Ameliorative Effect Of Probiotics On Uric Acid Metabolismmentioning
confidence: 99%
See 4 more Smart Citations
“…The activities of XOD were suppressed via a collaborative mechanism through some unknown specific effector substance secreted by Limosilactobacillus fermentum JL-3 in hyperuricemia mouse experiments. 25 A study of probiotics found that the excretion of uric acid in the urine increased by approximately 15% due to changes in xanthine and hypoxanthine levels after feeding Saccharomyces cerevisiae to lambs. 51 Lactobacillus brevis DM9218 was isolated from traditional fermented Chinese food and decreased serum uric acid levels and hepatic XOD activity in fructose-mediated hyperuricemia mice.…”
Section: The Ameliorative Effect Of Probiotics On Uric Acid Metabolismmentioning
confidence: 99%
“…A study in northwest China showed that Limosilactobacillus fermentum JL-3 isolated from traditional fermented foods (Jiangshui) can secrete uricase to decrease serum uric acid by up to 31.3% in vitro , which could significantly ameliorate hyperuricemia. 25 Three lactic acid bacteria strains, namely, Lactobacillus sp. OL-5, Lactobacillus plantarum Mut-7, and Lactobacillus plantarum Dad-13 were found to produce intracellular uricase in the gastrointestinal system and adapted to the environment or the stomach or intestines to remain active.…”
Section: The Ameliorative Effect Of Probiotics On Uric Acid Metabolismmentioning
confidence: 99%
See 3 more Smart Citations